High interleukin-35 expression is associated with the severity of rheumatic mitral stenosis - Wang, Ping; Li, Yaxiong; Zhao, Li; Liu, Bin; Cai, Zhibin; Zhang, Peng; Li, Peng; Gao, Xuezhen; Zhan, Yong (Frontiers in Immunology, 2025)
BackgroundRheumatic mitral stenosis (RMS) is the most common manifestation of rheumatic heart disease, with high morbidity and mortality. Interleukin-35 (IL-35) is a novel anti-inflammatory cytokine associated with many autoimmune diseases. However, the relation between IL-35 expression and RMS remains unknown. We aimed to study IL-35 expression in RMS and its association with disease progression.MethodsIL-35 concentration was analyzed in blood samples from 40 patients, including 20 moderate, 20 severe RMS, and 20 healthy controls by ELISA. Mitral valve (MV) IL-35 expression was determined by western blot and immunohistochemistry in patients with RMS (22 and 29 cases, respectively) in comparison to control specimens with mitral valve prolapsed (5 cases, respectively).ResultsIL-35 levels were significantly elevated in the blood of the RMS patients compared to those from healthy subjects(p<0.05) and positively correlated with the severity of RMS (r=0.317, p<0.05). The expression of IL-35 and its subunits (p35 and EBI3) was also detected in MV tissues of patients with moderate or severe RMS. The expression of IL-35 and its subunits (p35 and EBI3) had a positive association with the severity of RMS in MV tissues (r=0.528, p<0.01; r=0.561, p<0.001; r=0.456, p<0.01). Co-localization of p35 and EBI3 was seen in MV tissues of RMS patients in a predominantly perivascular pattern.ConclusionWe show for the first time an increase of IL-35 level in the blood and MV tissues of RMS patients, which is strongly correlated with the severity of RMS. These results suggest that IL-35 plays an important regulatory role in the progression of RMS.